Epizootic Rabbit Enteropathy (ERE): A Review of Current Knowledge - Puón-Peláez X-HD; McEwan NR; Olvera-Ramírez AM (European Scientific Journal, ESJ, 2018)
This literature review deals with Epizootic rabbit enteropathy (ERE), a condition which is potentially fatal to infected animals and continues to threaten the rabbit production industry internationally. The documented history of the condition is reviewed, together with what is known regarding the aetiology of the disease and candidate organisms which appear to be associated with its onset, although cannot be implicated as being the causal agent. Approaches to reduce the incidence of the condition (combining both husbandry practices and nutritional considerations), together with potential post-onset treatments and management strategies are also discussed.